The Existence of Equilibrium Asset Price Under Diverse Information - Sartono, R. Agus (Gadjah Mada International Journal of Business, 2005)
We investigate the effects of diverse information on the price of risky assets in rational expectation model. The expected cash flows innovation is considered as private information where informed trader knows it. It is assumed that the high informed trader has smaller variance error regarding the cash flows innovation than the low informed trader and uninformed traders. We found that the cash flow innovation influences the demand of informed trader. The market depth is a linear function of the demand of uninformed trader and weighted average of total variance error of information. Our finding supports previous research done by Spiegel and Subrahmanyam (1992).Our model shows that the more diverse the information, the higher the lambda coefficient which means the market becomes less liquid. The models consistent with Miller (1977) who found that the bigger the gap of private information is, the less liquid the market will be. If both informed traders have the same information they will demand the same amount of risky asset and it turns out to be similar as in the Kyle (1985) model.